2019
DOI: 10.1021/acs.nanolett.9b04719
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Calculation Guided Design of Single-Atom Catalysts toward Fast Kinetic and Long-Life Li–S Batteries

Abstract: Lithium−sulfur (Li−S) batteries are promising next-generation energy storage technologies due to their high theoretical energy density, environmental friendliness, and low cost. However, low conductivity of sulfur species, dissolution of polysulfides, poor conversion from sulfur reduction, and lithium sulfide (Li 2 S) oxidation reactions during discharge− charge processes hinder their practical applications. Herein, under the guidance of density functional theory calculations, we have successfully synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
401
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(439 citation statements)
references
References 39 publications
16
401
0
3
Order By: Relevance
“…In LSBs the cathode material is mainly sulfur, which is abundantly available, low cost, environmentally friendly and has high theoretical capacity of 1675 mAh g −1 . [ 1–6 ] However, the challenging issues associated with sulfur‐based cathodes are: 1) the low electrical conductivity of sulfur, 2) the dissolution and shuttling effects of lithium polysulfides (LiPs), and 3) large volume variations during charge/discharge cycles. These bring about low efficiency, poor cycling stability, self‐discharge phenomena, and ultimately degradation of the electrode material, all of which currently limit the potential commercialization of LSBs.…”
Section: Introductionmentioning
confidence: 99%
“…In LSBs the cathode material is mainly sulfur, which is abundantly available, low cost, environmentally friendly and has high theoretical capacity of 1675 mAh g −1 . [ 1–6 ] However, the challenging issues associated with sulfur‐based cathodes are: 1) the low electrical conductivity of sulfur, 2) the dissolution and shuttling effects of lithium polysulfides (LiPs), and 3) large volume variations during charge/discharge cycles. These bring about low efficiency, poor cycling stability, self‐discharge phenomena, and ultimately degradation of the electrode material, all of which currently limit the potential commercialization of LSBs.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen adsorption/desorption results (Supporting Information, Figure S1) indicated that abundant micropores can be identified in the host material, and the Brunauer-Emmett-Teller (BET) surface area and pore volume were 518.91 m 2 g À1 and 0.39 cm 3 g À1 ,r espectively.B y adopting the molten-diffusion method, we were able to encapsulate the Se/S into the CSH chambers.T EM image ( Figure 1b)o fC SH-S/Se revealed that Se/S particles can be identified within the hollow chamber,and the corresponding energy dispersive X-ray spectroscopy (EDS) mapping results ( Figure 1c)further confirmed the existence of Se and Sinside the hollow chamber.Furthermore,some Se/S wrapping on the shell can also be found, which is mainly caused by the high loading of Se/S and insufficient pore volume of CSH host. Uniformly dispersed Co atoms (Figure 1c)can be observed as well, which not only catalyzed the graphitization of carbon host to improve the electrical conductivity, [35] but also acted as additional binding and catalyzing sites to effectively immobilize the dissolved LiPSs/LiPSes [36] and catalyze the subsequent reduction reaction. [37] Theas-prepared cathode material is denoted as CSH-S/Se-x%(x is the weight ratio of doping Se in S/Se).…”
Section: Resultsmentioning
confidence: 97%
“…32,37,46 Recently, quantum dots have been regarded as a new approach to settle the drawbacks of Li-S batteries due to their abundant active sites, unique quantum connement effect and exceptional catalysis effect. [47][48][49] Xu and coworkers adopted black phosphorus (BP) quantum dots (QDs) in Li-S cathodes to chemically immobilize and catalyze the transition of LiPSs. 47 They conrmed that BP QDs achieved excellent adsorption ability to LiPSs and unexpected catalytic activity due to their stronger binding energies and the presence of more under-coordinated atomic structures of edge sites.…”
Section: Introductionmentioning
confidence: 99%
“…47 They conrmed that BP QDs achieved excellent adsorption ability to LiPSs and unexpected catalytic activity due to their stronger binding energies and the presence of more under-coordinated atomic structures of edge sites. [49][50][51] Pang and partners introduced N-doped carbon quantum dots (NCQD) into a modied separator in Li-S batteries, resulting in enhanced capacity retention and lower self-discharge. 48 These quantum dot-based research studies provide new ideas about Li-S batteries.…”
Section: Introductionmentioning
confidence: 99%